Importance of placental localisation in early pregnancy - Agrawal, Veena; Kulshresta, Sonal (Nepal Journal of Obstetrics and Gynaecology, 2008)
Objectives: To determine the incidence and rate of persistence of placenta praevia diagnosed as low lying placenta in d" 20 weeks’ gestation using sonography (USG) and to establish its’ co-relation with pregnancy outcome. Methods: Randomized 230 pregnant women studied by USG at d" 20weeks gestation. Among them 42 were recruited for study as they were having low lying placenta. These cases were rescanned at e" 28 weeks. Results: In 230 cases, the incidence of low lying placenta at d" 20weeks was18.26% (42/230); 90.5% had lateral, 2.4% had marginal and 7.1% had total placenta praevia. A total of 26 (61.9%) cases, had threatened abortion and two patients aborted. On longitudinal follow-up, 80% of remaining 40 cases had normally situated placenta at rescan. However those with total placenta praevia at d" 20weeks persisted as such with 100% persistence while only 10.5% with lateral low lying placenta persisted. APH was presentation in 3(7.1%), all of them undergoing cesarean sections for placenta praevia. Conclusion: Ultrasonography at < 20 weeks gestation showing low lying placenta has been useful in predicting placenta praevia at third trimester. Total placenta at this gestation has invariably persisted as placenta previa at third trimester. Key words: Placenta, Low lying Placenta, Placenta Praevia, APH doi:10.3126/njog.v2i2.1449 N. J. Obstet. Gynaecol 2007 Nov-Dec; 2 (2): 16 - 19